The Effect of the Tax Volunteer Program on the Tax Literacy Level of Individual Taxpayers: A Literature Study and Case Study of KPP Pratama Kembangan - Putri Permata Sari; Iwan Harefa; Yananto Mihadi Putra (Inisiatif Masyarakat Jurnal Indonesia (IMAJI), 2025)
The